2014
DOI: 10.1093/jxb/eru196
|View full text |Cite
|
Sign up to set email alerts
|

R2R3-MYB gene pairs in Populus: evolution and contribution to secondary wall formation and flowering time

Abstract: In plants, the R2R3-MYB gene family contains many pairs of paralogous genes, which play the diverse roles in developmental processes and environmental responses. The paper reports the characterization of 81 pairs of Populus R2R3-MYB genes. Chromosome placement, phylogenetic, and motif structure analyses showed that these gene pairs resulted from multiple types of gene duplications and had five different gene fates. Tissue expression patterns revealed that most duplicated genes were specifically expressed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 52 publications
3
48
1
Order By: Relevance
“…Together with their contrasting transcriptional responses to hormones and abiotic stress, our observations suggest that the gene duplication that gave rise to PaMYB32 and PaMYB33 was followed by a sub-functionalization of the paralogs, as predicted by the model on functional divergence of recently duplicated regulatory genes (Grotewold, 2005). Similar evolutionary changes have been observed for R2R3-MYB family TFs in several angiosperms (Dias et al, 2003; Chai et al, 2014; Zhao and Bartley, 2014). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Together with their contrasting transcriptional responses to hormones and abiotic stress, our observations suggest that the gene duplication that gave rise to PaMYB32 and PaMYB33 was followed by a sub-functionalization of the paralogs, as predicted by the model on functional divergence of recently duplicated regulatory genes (Grotewold, 2005). Similar evolutionary changes have been observed for R2R3-MYB family TFs in several angiosperms (Dias et al, 2003; Chai et al, 2014; Zhao and Bartley, 2014). …”
Section: Discussionsupporting
confidence: 75%
“…The more generalized late-biosynthesis-gene upregulation seen in PaMYB33 and PaMYB35 overexpression lines and the expression pattern of PaMYB30, PaMYB31, PaMYB33 , and PaMYB35 , which showed a higher degree of tissue specificity and more restricted responses to abiotic stress compared to PaMYB29 and PaMYB32 , suggests that these R2R3-MYB family TFs may perform their regulatory role in particular organs or distinct cell types. Such organ specificity is reported for Arabidopsis ' subgroup 7 R2R3-MYB members (Stracke et al, 2007), for paralogous R2R3-MYB genes, Pd MYB2 and Pd MYB20, in poplar (Chai et al, 2014) and to some extent among conifer subgroup 4 R2R3-MYB family TFs (Bedon et al, 2007, 2010). …”
Section: Discussionmentioning
confidence: 74%
“…A transcription factor, MlWRKY12 , from Miscanthus is involved in pith secondary wall formation and promotes flowering (Yu et al ., ). The expression of several poplar PdMYB genes in Arabidopsis affects secondary wall formation, and can either promote or delay flowering (Chai et al ., ). In this work, we observed that when PGX2 was overexpressed, PGX2 AT plants flowered earlier than Col controls, possibly due to enhanced expression of the flowering gene FT (Figure h).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, expression of MYB002 (an ortholog of AtMYB46 and AtMYB83), MYB021 (AtMYB46 and AtMYB83), MYB031 (AtMYB69), MYB090 (AtMYB52 and AtMYB54), MYB127 (AtMYB67), MYB128 (AtMYB103) and MYB158 (AtMYB69) (Chai et al, 2014;Zhao & Bartley, 2014) was significantly downregulated in PagKNAT2/6b OE plants. All of these genes could activate the expression of secondary wall biosynthesis genes, and their dominant repression transgenic plants showed altered secondary wall thickening of fibers and vessels in Arabidopsis (Zhong et al, 2007(Zhong et al, , 2008McCarthy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%